2020
DOI: 10.1080/09670874.2020.1779383
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification ofTrichogrammaspecies parasitizingOstrinia nubilalisin corn and pepper in south–east border of Europe

Abstract: The current study extends the faunistic survey of Trichogramma species parasitizing ECB to all agricultural growing regions in Serbia. Specimens of Trichogramma were reared from parasitized egg masses of ECB collected from field-grown corn and pepper crops. The number of egg masses parasitized varied by location. Using sequences of mitochondrial cytochrome oxidase I (COI) gene, we examined intra and interspecific variation in Trichogramma parasitizing the ECB egg masses. Seventy specimens were successfully seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The use of the multiplex assay in this study again demonstrated the widespread occurrence of 2 resident species of Trichogramma parasitizing the eggs of ECB. Coupled with the findings of surveys conducted in 2016 and 2018 (Ivezić et al 2018(Ivezić et al , 2020, it is clear that Trichogramma species, particularly T. brassicae, are important, naturally occuring egg parasitoids of ECB in Kikinda and other areas of Serbia. Indeed, natural rates of parasitism by Trichogramma spp.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The use of the multiplex assay in this study again demonstrated the widespread occurrence of 2 resident species of Trichogramma parasitizing the eggs of ECB. Coupled with the findings of surveys conducted in 2016 and 2018 (Ivezić et al 2018(Ivezić et al , 2020, it is clear that Trichogramma species, particularly T. brassicae, are important, naturally occuring egg parasitoids of ECB in Kikinda and other areas of Serbia. Indeed, natural rates of parasitism by Trichogramma spp.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies of the egg parasitoids of ECB in Serbian maize resulted in the identification of just two species, T. brassicae and T. evanescens (Ivezić et al, 2020). Identification in these studies was based on DNA sequences of the ITS2 and/or COI genes.…”
Section: Multiplex Pcr Designmentioning
confidence: 99%
See 3 more Smart Citations